Managing Resident Workforce and Education During the COVID-19 Pandemic: Evolving Strategies and Lessons Learned. Issue 2 (April 2020) - Schwartz, Andrew M.; Wilson, Jacob M.; Boden, Scott D.; Moore, Thomas J.; Bradbury, Thomas L.; Fletcher, Nicholas D.
Abstract : Background: The novel coronavirus and associated Coronavirus Disease 2019 (COVID-19) is rapidly spreading throughout the world, with robust growth in the United States. Its drastic impact on the global population and international health care is swift, evolving, and unpredictable. The effects on orthopaedic surgery departments are predominantly indirect, with widespread cessation of all nonessential orthopaedic care. Although this is vital to the system-sustaining measures of isolation and resource reallocation, there is profound detriment to orthopaedic training programs. Methods: In the face of new pressures on the finite timeline on an orthopaedic residency, the Emory University School of Medicine Department of Orthopaedics has devised a 5-pronged strategy based on the following: (1) patient and provider safety, (2) uninterrupted necessary care, (3) system sustainability, (4) adaptability, and (5) preservation of vital leadership structures. Results: Our 5 tenants support a 2-team system, whereby the residents are divided into cycling "active-duty" and "working remotely" factions. In observation of the potential incubation period of viral symptoms, phase transitions occur every 2 weeks with strict adherence to team assignments. Intrateam redundancy can accommodate potential illness to ensure a stable unit of able residents. Active duty residents participate in in-person surgical encounters and virtual ambulatory encounters, whereas remotely working residents participate in daily video-conferenced faculty-lead, case-based didactics and pursue academic investigation, grant writing, and quality improvement projects. To sustain this, faculty and administrative 2-team systems are also in place to protect the leadership and decision-making components of the department. Conclusions: The novel coronavirus has decimated the United States healthcare system, with an unpredictable duration, magnitude, and variability. As collateral damage, orthopaedic residencies are faced with new challenges to provide care and educate residents in the face of safety, resource redistribution, and erosion of classic learning opportunities. Our adaptive approach aims to be a generalizable tactic to optimize our current landscape.